Direct Medical Costs Related To Clinical Outcomes And Patterns Of Ischemic Stroke Drug Therapy In Panti Rapih Hospital Yogyakarta - Muslimah; Nina Anggraeni Noviasari; Nandhini Lawrence Anantaizaldy (International Journal of Health and Pharmaceutical (IJHP), 2022)
This study aimed to analyze clinical outcomes related to direct medical cost and the pattern of drug therapy. This was an analytical observational study with retrospective and concurrent data through observation from the perspective of the hospital. A total of 42 stroke ischaemic patients were enrolled in this study. Data were collected with a period of 1 year after the first stroke occurrence, which began on May 15th, 2019 until June 15th, 2020. Data sources used in this study include medical records, financial data, and drug data from pharmacies. Data were analyzed using the Mann-Whitney U test and the Kruskal-Wallis test. This study findings showed the highest sociodemographic data on age 41-70 years (54,76%), male (59,52%), length of stay of 5-10 days (66,60%), comorbid of hypertension (88,10%), complication of urinary tract infection (19,05%), CCI 3-5 (85,71%), condition at hospital admission of hemiparesis (83,72%), and Antiplatelet drug therapy (90,48%). Clinical outcomes of disability mostly occurred in males (59,52%), age 41-70 years (54,76%), and length of stay of 5-10 days (66,67%). There were 48 events of clinical outcomeincluding 14,29% recurrent stroke and disability (n=6), 100% disability (n=42) and no mortality (n=0). Recurrent stroke and disability were not associated with a direct medical cost per year, neither inpatient nor outpatient cost. This might be due to the severity of stroke at the hospital admission which not be considered in this study. In conclusion, this study’s findings could be used as consideration in the determination of health policy, health insurance, and data source for pharmacoeconomic.